Analisis Kebijakan Tata Ruang Kota dalam Menghadapi Tantangan Urbanisasi di Indonesia - Suci Indah Triani; Muhammad Aqil Al Hariri Lubis; Valina Sinka (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2025)
This study aims to explore public perceptions of urban spatial planning policies in addressing the impacts of urbanization in Medan. Data were collected using a 15-item Likert-scale questionnaire and analyzed descriptively, using proxy factor analysis (PCA), and using cross-demographic difference tests. The initial sample size consisted of seven respondents. The results showed strong recognition of the impacts of urbanization, such as increasing land pressure, slums, and limited infrastructure. The majority of respondents also supported data-driven spatial planning to address these issues. However, there were doubts about the effectiveness of government land conversion controls, which were considered suboptimal. Nevertheless, these results demonstrate the importance of public participation in urban planning. The internal reliability of this study was relatively low, with a Cronbach's alpha value of -0.112, making the findings exploratory in nature. The researchers recommend that this study be conducted with a larger sample size and further testing to obtain more representative and valid results, as well as to delve deeper into public perceptions of urban spatial planning policies.